PLAZMA PÜSKÜRTME YÖNTEMİYLE OLUŞTURULAN AL2O3- TİO2 KOMPOZİT KAPLAMALARIN MİKROYAPI KARAKTERİSTİKLERİ - Buytoz, Soner; Ersöz, Emine; Islak, Serkan; Orhan, Nuri; Kurt, Bülent; Somunkıran, İlyas (International Iron & Steel Symposium, 02-04 April 2012, Karabük, Türkiye, 2012)
Yapılan çalışmada, SAE 1040 çeliğine plazma püskürtme yöntemiyle, Al2O3 tozu ve değişen oranlarda TiO2 tozu ilave edilerek Al2O3/TiO2 kompozit kaplamaları oluşturuldu. Elde edilen kaplama tabakalarının metalografi incelemeleri neticesinde lamelli bir mikroyapı içerisinde az miktarda ergimemiş partiküller, kısmi ergimiş ve tamamen ergimiş bölgeler gözlendi. Al2O3-TiO2 kompozit kaplamalarında TiO2 toz miktarının artmasına karşı gözenek miktarının azaldığı tespit edildi. XRD analizi sonuçları, kaplama tabakasında γ -Al2O3, α-Al2O3, Al2TiO5, ve TiO2 (rutil) fazlarının oluştuğunu göstermiştir. Kaplama tabakasının mikrosertliği alt malzemeye göre 3-4.5 kat daha fazladır. Kaplama tabakalarının ortalama mikrosertlik değerleri 650-850 HV arasında değişmiştir.In this study, Al2O3-TiO2 composite coatings were thermally sprayed on the SAE 1040 steel using atmospheric plasma spray (APS) process of mixed different rates of micron–sized TiO2 and micron-sized Al2O3 powders. The effects of TiO2 addition on the microstructure, phase compositions and microhardness of the coatings were investigated by using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffractometry (XRD) and microhardness tester. The results show that the Al2O3-TiO2 composite coatings consist of both fully melted regions, partially melted regions, and the unmelted particles in regions of lamellar-like structure. Phase transformations from mainly stable α-Al2O3 and anatase-TiO2 in the powders to predominant metastable γ-Al2O3, rutile-TiO2 and Al2TiO5 phase in the Al2O3-TiO2 composite coatings were observed. It was idendified that the pore content was decreased with increase of TiO2 powder ratio. The microhardnesses of the coating layers were found to be 3-4.5 times higher than that of substrate material. The average microhardness values of the coatings were changed as 650-860 HV.
Keywords: Plazma püskürtme, Al2O3/TiO2 kompozit kaplamaları, mikroyapı